Strengthening Customary Forest Rights for Indigenous People in Indonesia Green Constitution Framework - Xavier Nugraha; Angelica Milano Aryani Wibisono; Alissa Angelia; Bryan Owen S.; Putri Riska Answendy (University of Jember, Indonesia, 2023)
The ongoing struggle of indigenous people fighting for their rights to preserve the customary forests underscores the critical need to protect both cultural heritage and environment. This research focuses on implementing the Green Constitution in Indonesia, aiming to strengthen the existence of indigenous peoples and their customary rights to customary forests. However, there are significant problems with Article 33(3) of the 1945 Constitution which emphasizes the welfare of the people through the exploitation of natural resources, often neglecting aspects of environmental conservation and contradicting Indonesia's commitment to the Sustainable Development Goals (SDGs). As a result, the Indonesian Constitution has an anthropocentric orientation that prioritizes environmental preservation for human interests rather than fully reflecting the Green Constitution principles that emphasize environmental sustainability in line with human needs. The research used in this study is juridical-normative approach to analyze the law and relevant regulation regarding the issue at hand to identify possible solution towards the existing legal issues. This research identifies two main problems: first, to what extent the 1945 Constitution reflects the principles of the Green Constitution, and second, how efforts to strengthen the rights of indigenous peoples to customary forests reflect the Green Constitution. The results show that the 1945 Constitution has not fully adopted the principles of the Green Constitution, therefore measures are needed to strengthen the rights of indigenous peoples related to customary forests, including the elimination of conditional recognition through judicial interpretation of Article 18B paragraph (2) of the 1945 Constitution, to secure environmental conservation democratically and sustainably.